Studies on proximity effect in Mo/Bi1.95Sb0.05Se3 hybrid structure. (25th May 2016) - Amaladass, E P; Sharma, Shilpam; Devidas, T R; Mani, Awadhesh
Abstract: Proximity effect in a mechanically exfoliated Bi1.95 Sb0.05 Se3 topological insulator (TI) single crystal partially covered with disordered superconducting (SC) Mo thin film is reported. Magneto-transport measurement was performed simultaneously across three different regions of the sample viz. SC, TI and SC / TI junction. Resistance measured across SC shows a T C at 4.3 K concomitantly the resistance measurement on TI showed a metallic trend with a steep upturn at T C . Magneto-resistance (MR) measurement on TI exhibit a positive MR with Shubnikov-de Haas (SdH) oscillations, whereas on SC a positive MR superimposed with steep cusp close to T C is observed. Across SC/TI junction both SdH oscillation and the cusp were observed. The frequency of SdH oscillation on SC / TI junction is found to be lesser ( 125 T) as compared to a reference Bi1.95 Sb0.05 Se3 sample ( 174 T). Upper critical field HC2 deduced from WHH fit was found to be 17.14 T for a reference Mo film whereas Mo film deposited on TI showed a decreased H C2 of 4.05 T. The coherence length for the former was found to be 4.38 nm and for the latter 9.01 nm. The interaction between the spin-less Cooper pairs in SC with the spin-momentum locked carriers on the surface of TI is believed to cause such changes in transport properties.